Transcriptome Analysis of Cinnamomum chago: A Revelation of Candidate Genes for Abiotic Stress Response and Terpenoid and Fatty Acid Biosyntheses - Zhang, Xue; Zhang, Yue; Wang, Yue-Hua; Shen, Shi-Kang (Frontiers in Genetics, 2018)
Cinnamomum chago, an endangered species endemic to Yunnan province, possesses large economic and phylogenetic values in Lauraceae. However, the genomic information of this species remains relatively unexplored. In this study, we used RNAseq technology to characterize and annotate the C. chago transcriptome and identify candidate genes involved in special metabolic pathways and gene-associated simple sequence repeats (SSRs) and single-nucleotide polymorphism (SNP). A total of 129,097 unigenes, with a mean length of 667 bp and an N50 length of 1,062 bp, were assembled. Among these genes, 56,887 (44.07%) unigenes were successfully annotated using at least one database. Furthermore, 47 and 46 candidate genes were identified in terpenoid and fatty acid biosyntheses, respectively. 22 candidate genes participated in at least one abiotic stress response of C. chago. A total of 25,654 SSRs and 640 SNPs were also identified. Based on these potential loci, 55 novel EST-SSR primers were successfully developed. This work provides comprehensive transcriptomic data that can be used to establish a valuable information platform for gene prediction, signaling pathway investigation, and molecular marker development for C. chago and other related species. Such platform can facilitate further studies on germplasm conservation and utilization of Lauraceae specice